2014
DOI: 10.1007/s00408-014-9669-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum Surfactant Protein D (SP-D) is a Prognostic Marker of Poor Outcome in Patients with A/H1N1 Virus Infection

Abstract: Our results revealed that higher circulating levels of SP-D are associated with higher mortality risk in critically ill A/H1N1 patients. SP-D might be a predictive factor of poor outcomes in viral pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 32 publications
(41 reference statements)
3
32
0
Order By: Relevance
“…SP-D as a marker for severity of pneumonia also has been studied before. [ 29 31 ] In accordance with the study of Leth-Larsen et al, we found SP-D levels to be significantly lower on day 0 in CAP patients compared to levels of healthy controls. [ 29 ] In contrast, two other studies showed high SP-D levels in respectively critically ill patients with acute respiratory distress syndrome (ARDS) suffering from A/H1N1 infection and CAP patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…SP-D as a marker for severity of pneumonia also has been studied before. [ 29 31 ] In accordance with the study of Leth-Larsen et al, we found SP-D levels to be significantly lower on day 0 in CAP patients compared to levels of healthy controls. [ 29 ] In contrast, two other studies showed high SP-D levels in respectively critically ill patients with acute respiratory distress syndrome (ARDS) suffering from A/H1N1 infection and CAP patients.…”
Section: Discussionsupporting
confidence: 90%
“…[ 29 ] In contrast, two other studies showed high SP-D levels in respectively critically ill patients with acute respiratory distress syndrome (ARDS) suffering from A/H1N1 infection and CAP patients. [ 31 , 32 ] This difference in findings could be caused by the moment of sampling and/or that the study of Delgado et al was performed in patients with ARDS, while our study excluded patient who were directly admitted to the intensive care unit (ICU). Lower SP-D levels found on day 0 might be due to less SP-D production by pneumocytes as a result of pulmonary infiltrates.…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, circulating surfactant protein levels may have clinical usefulness. One study demonstrated that surfactant protein levels can be used as an indicator of lung injury and poor outcomes in H1N1 viral infections (47), and another showed that SP-A and SP-D levels are elevated in those with pulmonary fibrosis compared with healthy volunteers (48).…”
Section: Pulmonary Disorders Related To Surfactant Dysfunction or Defmentioning
confidence: 99%
“…We demonstrated that serum SP-D concentrations are significantly reduced by chemotherapy in patients with pediatric ALL reaching a nadir on days 15-22 coinciding with a nadir of the white blood cell have been related to several different pulmonary pathologies and respiratory outcomes. [30][31][32][33][34] Previous studies indicated an association between circulating SP-D levels and mortality in elderly women 35 and A/H1N1-infected patients, 36 prognosis in patients with chronic kidney disease, 37 and cardiovascular morbidity and mortality. 38 In rheumatoid arthritis, SP-D levels are below normal in newly diagnosed and untreated patients, and are inversely correlated with systemic inflammation suggesting that low systemic SP-D levels may be involved in the initiation or maintenance of the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%